The barrio in Navarra's fiction - Gimenez-Maceda, Teresita (1977)
Tuyom is a small barrio in Carcar, Cebu, that juts out to the sea. Typical of the condition in many parts of Cebu, its land is diy and barren. Life is extremely difficult and, to survive, its people resort to fishing, Cuba-gathering, and selling copra and maguey. The place is poor and the people remain poor. The hardships and sufferings of the people of his barrio, Tuyom, their struggles to survive, are the concerns of Marcel M. Navarra, ?father of modem Cebuano writing.?' Writing from 193 l to 1955 for vernacular magazines (mainly for Bisaya), Navarra probed into his people?s problems and thoughts in search for some meaning to the bitter and oppressed lives they lead. Viewed in their totality, his stories express a compelling vision of life in the barrio.
Includes bibliographical references.
Keywords: Navarra, Marcel M. -- Criticism and interpretation; Short stories, Cebuano -- Translations into English; Short stories, Cebuano -- Translations into Pilipino; Short stories, Cebuano; Short stories, English -- Translations from Cebuano; Short stories, Pilipino -- Translations from Cebuano